Communication Activities Seba Baduy Lebak Regency Banten - M. Ali Syamsuddin Amin (Budapest International Research and Critics University, 2020)
The research is intended to elaborate vastly concerning communication activity ceremony of Seba Baduy in Lebak Banten Region. Focusing on some issues which divided into few micro subs such as communicative situation, communicative event and communicative act in Seba Baduy ceremony, Lebak Banten Region. The Applied method for the project is qualitative method of communication Ethnographic. The subject of the research is Baduy and Jaro Luar community which follows Seba Baduy ceremony, there are 3 informants obtained by purposive technique in the researched ceremony. The data gathering requirement held through in-depth interview, non-participant observation, field notes, literature study, documentations and daring searching. The technique of testing the validity of data by increasing the persistence of observation, triangulation and discussion among friends. For the analytical data used are descriptive, analytical, and interpretation. Research result shows that communicative situation found in the Seba Baduy ceremony which held on two spots Pendopo of Lebak Region and Pendopo of Banten Province on Safar month. Communicative event in the Seba Baduy ceremony as the gratitude and do what the ancestors of Baduy community have passed through generations. While communicative acts in Seba Baduy is act which shows verbal and non-verbal acts as respect expression for the Government and appreciate the nature.